Multiscale interfacial stabilization via prelithiation separator engineering for Ah-level anode-free lithium batteries - Ahu Shao; Helin Wang; Min Zhang; Jiacheng Liu; Lu Cheng; Yunsong Li; Yuxiang Guo; Zhiqiao Wang; Qiurong Jia; Xin Wang; Xiaoyu Tang; Xiaodong Zhao; et al. (Nature Communications)
Abstract Anode-free lithium batteries represent a promising avenue for high-energy-density storage, yet their practical application is hindered by lithium inventory loss from parasitic interfacial reactions, cathode degradation, and limited Li+ reversibility. Herein, we propose a polyolefin separator integrated with a Li2S@C sacrificial layer, achieving multiscale interfacial stabilization in Ah-class anode-free pouch cells. This approach simultaneously replenishes the customized Li+ inventory during the formation cycle and establishes the lithium polysulfide-containing cathode interface with high-voltage tolerance (till 4.5 V). Real-time tracking via in-situ electrochemical impedance spectroscopy and transmission-mode operando X-ray diffraction reveals accelerated Li+ diffusion kinetics and stabilized phase evolution in LiNi0.8Co0.1Mn0.1O2 cathode interfaced with Li2S@C|PE prelithiation separator. Consequently, a 1.22 Ah pouch cell with an Ag-modified Cu foil and LiNi0.8Co0.1Mn0.1O2 cathode is assembled with Li2S@C|PE separator and exhibits gravimetric and volumetric energy densities of 450 Wh kg-1 and 1355 Wh L-1, respectively. This prelithiation protocol demonstrates upscaling potential and generic applicability to secure the interfacial chemistries for anode free/less lithium metal batteries.